2005
DOI: 10.1002/cphc.200400605
|View full text |Cite
|
Sign up to set email alerts
|

Percolating Microemulsions of Nonionic Surfactants Probed by Dielectric Spectroscopy

Abstract: [a] Microemulsions are thermodynamically stable, isotropic transparent fluids of two immiscible liquids and a surface-active agent. They have been thoroughly investigated over the last few decades not only with respect to possible industrial applications but also due to their great theoretical interest. [1,2] On the oil-rich side of the phase diagram reverse micelles are formed which, in a first approximation, can be described as spherical water droplets with typical diameters in the range of % 10-60 nm, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…As can be seen in Figure IV-8, the lower curve is not linear over the whole range, and such behavior has also been described in literature before. 246 In that case, s was determined to be 1.28, which is in better agreement with the model of dynamic percolation. However, this is only a rough estimation, because the slope of the curve determining s depends on the number of points that are taken into account.…”
Section: Iv22 Investigations At Ambient Temperature -86 -supporting
confidence: 74%
See 1 more Smart Citation
“…As can be seen in Figure IV-8, the lower curve is not linear over the whole range, and such behavior has also been described in literature before. 246 In that case, s was determined to be 1.28, which is in better agreement with the model of dynamic percolation. However, this is only a rough estimation, because the slope of the curve determining s depends on the number of points that are taken into account.…”
Section: Iv22 Investigations At Ambient Temperature -86 -supporting
confidence: 74%
“…Such differences between the experimental and the theoretical value have already been observed in literature. 245,246 As the exponent μ is almost the same for these two models, it cannot be used for a clear differentiation between the theoretical values. As can be seen in Figure IV-8, the lower curve is not linear over the whole range, and such behavior has also been described in literature before.…”
Section: Iv22 Investigations At Ambient Temperature -86 -mentioning
confidence: 99%
“…138 When approaching the percolation point via changing the temperature one observes a divergence of the static permittivity Δε ∼ (T p − T) −s at the percolation temperature T p with a universal exponent s for approaching from either side. 139 2.1.10. Interfacial Tension (IFT).…”
Section: Survey Of Techniques For Characterizing Microemulsionsmentioning
confidence: 99%
“…Only the faster process is changed when percolation takes place and then becomes substantially slowed down . When approaching the percolation point via changing the temperature one observes a divergence of the static permittivity Δε ∼ ( T p – T ) −s at the percolation temperature T p with a universal exponent s for approaching from either side …”
Section: Characterization Of Microemulsionsmentioning
confidence: 99%
“…Dielectric relaxation spectroscopy (DRS) is a powerful method to study the physicochemical properties of micelles and microemulsions. Asami studied the TX-100/water mixtures by DRS over wide ranges of temperatures and TX-100 concentrations and found that 2–3 water molecules hydrated with every TX-100 molecule. The dielectric experiments reported by Bhattacharya et al favored the static percolation model to describe the behavior of the permittivity.…”
Section: Introductionmentioning
confidence: 99%